(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
In the last 30 years, neurosciences, with their mechanistic approach, have dealt with the study of freedom of the will, a field that is considered typical of philosophy or psychology. The studies in neurosciences have been paradoxically appreciated more by philosophers and psychologists than by the scientists themselves, who have straightened the methodological limits. From the considerations of those limits, coming precisely from the neurosciences themselves, rises an interpretation of the freedom of the will that throws a bridge towards positions that are considered typical of philosophical and psychological theories.